Hubungan Perilaku Makan dan Konsumsi Tablet Fe dengan Kejadian Anemia pada Ibu Hamil di Kabupaten Fakfak Papua Barat - Kristiawan P.A. Nugroho (LPPM STIKES Guna Bangsa Yogyakarta, 2017)
Background: Anemia is associated with a condition of blood deficiency or low red blood cell count. Anemia during pregnancy is important to note because it concerns public health, especially maternal and child health.